Capim elefante cultivado em solo ácido com aplicação de gesso com alternativa fitoenergética para o Pólo Gesseiro do Araripe/PE. - SANTOS, Renato Lemos dos (2011)
The cultivation of elephantgrass on Araripe plain in Pernambuco can be an alternative source of energy for calcination of gypsite. The region has a predominance of acidic Oxisols with high exchangeable Al in the subsurface, which is toxic for crops. The practice more feasible to reduce the toxicity of excess aluminum in that layer is the application of gypsum. Due to its mobility, the gypsum can be applied in the surface for acting in the subsurface soil. Therefore, the aim of this work was to assess the use of elephantgrass as an alternative source of energy as well as the implications of using mineral gypsum in the production of biomass and soil remediation. Thereby, the experiment was composed by three varieties of elephantgrass, such as, Cameroon, Gramafante and Roxo in the presence and absence of mineral gypsum through a factorial arrangement (3 x 2), with treatments arranged in 4 randomized blocks. The research was conducted at the Experimental Station of the Agronomic Institute of Pernambuco in Araripina/PE. The soil in the experimental area was classified as Oxisol of sandy loam texture class. At 128 days after planting was collected the leaf +3 for assessment of nutritional status of grass, at 213 days it was cut and measured the output of dry matter, nutrient content in the biomass, quantity extracted and efficiency of utilization of these nutrients, the levels of Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), lignin, moisture, higher heating value (HHV) of the varieties of grass, and also the energy yield of grass in the calcination of gypsite. Furthermore, after 221 days of treatment application, soil samples were collected at two depths (0.0-0.2 and 0.2-0.4 m) for evaluating the effect of mineral gypsum and cultivation of different varieties of elephantgrass on soil chemical characteristics. Cameroon elephantgrass was more demanding in Ca, K and P and the Gramafante grass in S. The Cameroon and Gramafante elephantgrass showed high yields of dry matter. Only the Cameroon variety had the production increased by application of mineral gypsum. As a result, this variety achieved 33 Mg ha-1 of dry matter. Gramafante elephantgrass can be recommended to the environments with restrictive availability of Ca and Mg and rich in S, and despite having higher content lignin and PCS, the largest energy production by unit area was observed by the Cameroon grass, that is recommended as an alternative source of energy for the region of the Gypsum Pole of the Araripe in Pernambuco. The levels of Ca2+, S-SO42-, Al3+ and its saturation were not affected by the application of mineral gypsum at subsurface. There was not leaching of Mg2+ and K+ of surface layer. The application of mineral gypsum reduced the pH of the soil at layer subsurface. The Cameroon cultivation provokes the increase in soil pH, reducing the Al content and saturation. The cultivation of this variety is recommended for the acid soils in the Plain Araripe, mainly as an alternative source of energy for calcination of gypsite for being useful in industrial processes of the Gypsum Pole of Araripe.